TO STUDY AND SIMULATION OF DUAL BAND H SHAPED RECTANGULAR MICROSTRIP PATCH ANTENNA USING VARIOUS PARAMETER - Mansoori, Saima; Koshta, Rahul (International Journal of Engineering Technologies and Management Research, 2017)
The substrate which is the first step in designing a patch antenna. Teflon (dielectric constant = 1.33 and height = 3.6 mm) are used as subs for the purpose of designing of Dual Band H Shaped Rectangular Microstrip Patch Antenna. The dimension of patch, ground plane, feed line width, inset notch etc. the design have important effects on the impedance matching.